Analysis of the Effect of Work Stress and Non-Physical Work Environment on Teacher Performance - Supriyadi Supriyadi; Lukmanul Hakim; Linda Septarina (eCo-Buss, 2022)
This study aims to determine the impact of work stress and non-material work environment on teachers' performance in Bandar Lampung High School. The population of this study is high school teachers in Bandar Lampung and a sample of 42 teachers was used. Data analysis techniques used included testing the validity and reliability of data instruments, techniques for data collection by observation and questionnaires, and data analysis techniques including tests for linearity, normality, multicollinearity, and multiple linear regression analysis. The results of this study suggest that job stress and non-manual work environment have a positive impact on the performance of teachers at Bandar Lampung High School.